Accessibility and Update Status of Published Software: Benefits and Missed Opportunities - Huang, Xunhe; Xie, Jieru; Otecko, Newton O.; Peng, Minsheng (Frontiers in Research Metrics and Analytics, 2017)
Online accessibility and continuous updating of software packages is important for their application and resource-sharing. We evaluated the accessibility and update status of 214 software packages published in Molecular Ecology Resources in the past fifteen years (2001-2015), and report the associated benefits and missed opportunities. Original publications describing these software packages have been cited 31,886 times in total, with 19.6% of them being cited more than 100 times. However, 41.6% (89/214) of the source websites provided in the original papers were inaccessible, of which only 29.2% (26/89) had alternative websites. Up to 63.1% (135/214) of the software packages had not been updated since their publication or were inaccessible. A huge disparity in accessibility, 100% (41/41) vs. 63.6% (110/173), was observed between websites deposited in long-term servers vs. academic institution websites, personal homepages or e-mails, respectively. In addition, software packages that were accessible and updated were significantly more likely to be cited, compared to those that were inaccessible and un-updated. By guaranteeing the accessibility of their published software packages, for instance by depositing them in long-term servers, and keeping the software packages updated, software developers will further resource-sharing, and promote reproduction and citation of their software.